Solar Powered UV Light Pest Management for Sustainable Agriculture - Mohd Zamri, Muhammad Aimal Fiqri; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2024)
This project addresses the creation and application of an ultraviolet (UV) light system that runs on solar power for the purpose of controlling pests in agricultural environments. The main goal is to reduce insect populations that have an impact on crop output in an environmentally sustainable manner. UV lamps are powered by solar energy and are used by the system to attract and trap different types of agricultural pests. The solar-powered UV light trap's design, constructing, and testing are all included in the research. The design prioritizes increasing the attraction rate of bugs and boosting energy efficiency.  Choosing the right materials and putting the solar panels, UV lights, and trapping devices together are part of the construction step. Field tests are used in testing to evaluate the system's performance in actual agricultural settings. The outcomes show that, without the use of dangerous chemicals, the solar powered UV light pest management system is successful in dramatically lowering pest populations. By using only renewable solar energy, the system reduces the environmental effect. The results imply that this innovative approach can improve agricultural sustainability and production.